2010
DOI: 10.3184/030823410x12792754099464
|View full text |Cite
|
Sign up to set email alerts
|

Facile Access to Optically Active Ring C Aromatic Diterpenes from (+)-manool. Synthesis of (+)-13-Hydroxypodocarpa-8,11,13-Triene, (+)-7-Deoxynimbidiol and (+)-Nimbidiol

Abstract: A practical method for the synthesis of naturally occurring ring C aromatic diterpenes from (+)-manool via key intermediate β-enone is described. The natural (+)-13-hydroxypodocarpa-8,11,13-triene, the antitumour (+)-7deoxynimbidiol, and (+)-nimbidiol were prepared in good overall yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…The synthetic route used to achieve the target compounds is shown in Scheme 1. According to the procedure previously reported by us, the key intermediate 2 was obtained in two steps from (+)-manool 1, via ozonolysis 16 and intramolecular condensation, 17 and intermediate 3 was obtained in three steps from compound 2, via aromatisation, 16 protection 18 and benzylic oxidation. 18 Reaction of 3 with trimethylsilyl cyanide (TMSCN) in the presence of the KCN/18-crown-6 complex at room temperature for 8 h (Method A) followed by dehydration with POCl 3 gave compound 4 in 70% yield.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The synthetic route used to achieve the target compounds is shown in Scheme 1. According to the procedure previously reported by us, the key intermediate 2 was obtained in two steps from (+)-manool 1, via ozonolysis 16 and intramolecular condensation, 17 and intermediate 3 was obtained in three steps from compound 2, via aromatisation, 16 protection 18 and benzylic oxidation. 18 Reaction of 3 with trimethylsilyl cyanide (TMSCN) in the presence of the KCN/18-crown-6 complex at room temperature for 8 h (Method A) followed by dehydration with POCl 3 gave compound 4 in 70% yield.…”
Section: Resultsmentioning
confidence: 99%
“…Only the podocarpa-13-nitrile 9 exhibited significant inhibition of NO production (IC 50 = 6 µM) but no cytotoxicity Scheme 1 (i) Ref. 16,17 (2 reaction steps); (ii) Ref. 16,18 activity in RAW 264.7 cells in the range of concentrations evaluated, as well as weak cytotoxic activity in HT-29 and PC3 cells.…”
Section: Cytotoxic Activitymentioning
confidence: 99%
“…In 2007, Jaiswal et al 22 suggested that (+)-totarol 19 may be useful as a lead compound to develop an effective antitubercular drug. The phenol (+)-13-hydroxypodocarpa-8,11,13-triene 20 was isolated from the bark of Taiwania cryptomeriodes in 2000 by Kuo et al 23 In 2010, Villamizar et al 24,25 reported the synthesis of (+)-nimbidiol 3, 7-deoxynimbidiol 5 and (+)-13-hydroxypodocarpa-8,11,13-triene 20 from (+)-manool 1 using the α,βunsaturated ketone 22 as a key intermediate (Scheme 6). The alcohol 1 was oxidised with anhydrous potassium permanganate in the presence of a phase transfer catalyst, trimethylphenylammonium chloride, to obtain ketone 6 in 90% yield.…”
Section: Ring C Aromatic Diterpenesmentioning
confidence: 99%
“…61,62 Manool has provided the starting material for the synthesis of some butenolides, potential anti-malarial peroxides and ring C aromatic diterpenes. 63,64 The synthesis of the (+)-leopersin D from sclareol established its absolute stereochemistry. 65 Sclareol also formed the starting material for a synthesis of the meroterpenoid (+)-makassaric acid, 66 some spongiane analogues 67 and cheilanthane sesterterpenes.…”
Section: Labdanesmentioning
confidence: 99%